Determinant of earnings management practices in manufacturing companies - Mulia, Firnanda Kasih; Leniwati, Driana; Wicaksono, Agung Prasetyo Nugroho (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This study aims to examine the effect of audit committees, independent commissioners, and the presence of women on boards, such as the chief executive officer and chief financial officer, on earnings management practices.Design/Methodology/Approach: This research used a quantitative method with a final panel data sample of 25 companies in the manufacturing sector for three years from 2020 to 2022. Hypothesis testing employed the regression model with the Common Effect Model (CEM) test. Sampling was conducted using secondary data on the Indonesia Stock Exchange (IDX) and each company's website.Research findings: The results of the study demonstrated that independent commissioners, independent audit committees, audit committee expertise, audit committee activities, and audit committee size yielded a significant effect on earnings management practices, while female CEOs and female CFOs had no significant impact on earnings management practices.Theoretical contribution/Originality: This research develops a theory that previously did not exist; in this research, the authors used asymmetric information theory to test the independent and dependent variables. Additional variables by suggestions in previous research are provided; therefore, it is hoped that this can strengthen the results of prior research. Practitioner/Policy implication: The practical implication of this research is that the existence of an independent audit committee with a positive influence on earnings management can improve the company's financial performance, make it easier for managers or internal company parties to make better decisions in the future, and meet performance targets set by other parties, such as investors and creditors. Profit management can also be used to obtain tax benefits. During the previous pandemic, the government implemented tax compensation for taxpayers who met the criteria.